Co-ordination Complexes of Tetradentate N2O2 Donor Macrocyclic Ligand (b,i) Dibenzo-m-(dinitrobenzo)5,8- diaza, 1,12-dioxocyclotetradeca 4,8-diene with Cu(II), Ni(II), and Co(II) - Srivastava, Sadhna; Ahmad, Nihal; Shukla, P.R. (Asian Journal of Chemistry, 2010)
Twelve new tetracoordinated macrocyclic complexes of Cu(II), Ni(II) and Co(II) possessing the general formulae {M(L)}X2and {Co(L)(H2O)2}X2 where L ═ title macrocyclic ligand, M ═ Cu(II) and Ni(II) and X ═ Cl–, SCN–, BF4– and ClO4– have been prepared. The complexes have been characterised using elemental analysis, molar conductance, IR spectra, magnetic measurements and electronic spectral studies. The complexes of Cu(II) and Ni(II) were assigned to have square planar structures whereas the Co(II) complexes are octahedral by the axial coordination of two water molecules.